2020
DOI: 10.1109/access.2020.2978621
|View full text |Cite
|
Sign up to set email alerts
|

Computation of Power Extraction From Photovoltaic Arrays Under Various Fault Conditions

Abstract: Photovoltaic (PV) faults such as partial shading, bypass-diode defects, degradation of PV modules, and wiring issues greatly affect the power output and cause various peaks in P-V curves of a PV system. Although, commonly used Total-Cross-Tied (TCT) scheme in PV arrays is considered instrumental for reducing power losses there lies a great scope to evaluate power extraction through reconfiguration of modules with different PV materials. This paper presents detailed investigation of power extraction using numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…During the first 2 months, the soiling ratio decreased by less than 2.5%. The PV module reconfigurations using copper indium gallium selenide (CIGS) and polycrystalline PV technology have been examined in the study (Ul-Haq et al, 2020). This report also includes a thorough quantification of the effects of the investigated PV problems on the electricity system.…”
Section: Polycrystalline and Bifacial Modulesmentioning
confidence: 99%
“…During the first 2 months, the soiling ratio decreased by less than 2.5%. The PV module reconfigurations using copper indium gallium selenide (CIGS) and polycrystalline PV technology have been examined in the study (Ul-Haq et al, 2020). This report also includes a thorough quantification of the effects of the investigated PV problems on the electricity system.…”
Section: Polycrystalline and Bifacial Modulesmentioning
confidence: 99%
“…If there were some problems in the PV system structure or wiring, the resistance between two points might be low, and it leads to short circuit and harms the PV system [115]. This fault is usually detected by analyzing power voltage characteristic curves [116]. Like line to line fault, number of the studies in which bridging fault is found and analyzed by machine learning approaches has been considerably lower than ones.…”
Section: Bridgingmentioning
confidence: 99%
“…The study conducted by Ul-Haq et al [45] targeted the determination of the amount of extracted power from PV solar modules under different fault types using P-V curve analysis. Several types of interconnections were investigated, including Series-Parallel (SP), Total-Cross-Tied (TCT), Bridge-Link (BL), and Reconfiguration Method (RM).…”
Section: Bridgingmentioning
confidence: 99%